English for Specific Purposes in Hotel and Tourism Management: A Need Analysis - S, Sabari Sankar; B R, Aravind (International Journal of Language and Literary Studies, 2026)
The English language which is the most widely used language in the international hospitality industry, has a massive impact on its development. Hotel and tourism management graduates should be adequately understanding of their vital abilities and have a strong command of English in the industry. Many investigations have been undertaken on existing ESP courses in various fields. Though little research has been completed on ESP in Hotel Management, significant gaps exist in the design of ESP courses to meet the demands of L2 learners. The current study partially sought to assess the linguistic needs of undergraduate hotel and tourism management students based on their desires, deficiencies, and requirements. The current study used a mixed-methods approach, utilizing Google Forms questionnaires. It containing both Likert scale and open-ended items. The methodology used data triangulation to assess students' wants (what they want to learn), lacks (gaps between present and necessary competency), and necessities (objective criteria for job effectiveness). Despite the fact that wants, lacks, and necessities were not highly similar, the findings indicated that all four language skills should be emphasized in ESP courses, with speaking and listening abilities being especially important for professional development. However, these findings are based on a modest sample size (N=40), which may limit its generalizability to broader contexts.